Education and social education - Rizaeva Husniya Ubaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
In  this  article,  opinions  are  given  about  the  types  of  education  and  social  education,  their  place  in  society.  Information  about  the  importance  and  necessity of education, the scientific traces of the scholars of the East in this matter are  presented.